Equilibrium crystallization of massif-type anorthosite residual melts: a case study from the 1.64 Ga Ahvenisto complex, Southeastern Finland - Fred, Riikka; Heinonen, Aku; Heinonen, Jussi S. (Contributions to Mineralogy and Petrology, 2020)
Fe–Ti–P-rich mafic to intermediate rocks (monzodiorites and oxide–apatite–gabbronorites, OAGNs) are found as small intrusions in most AMCG (anorthosite–magnerite–charnokite–granite) suites. The origin of the monzodioritic rocks is still debated, but in many studies, they are presumed to represent residual liquid compositions after fractionation of anorthositic cumulates. In the 1.64 Ga Ahvenisto complex, SE Finland, monzodioritic rocks occur as minor dike-like lenses closely associated with anorthositic rocks. We report new field, petrographic, and geochemical (XRF, ICP-MS, EMPA) data complemented with crystallization modeling (rhyolite-MELTS, MAGFRAC) for the monzodioritic rocks, apatite–oxide–gabbronorite, and olivine-bearing anorthositic rocks of the Ahvenisto complex. The presented evidence suggest that the monzodioritic rocks closely represent melt compositions while the apatite–oxide–gabbronorite and olivine-bearing anorthositic rocks are cumulates. The monzodioritic rocks seem to form a liquid line of descent (LLD) from primitive olivine monzodiorites to more evolved monzodiorites. Petrological modeling suggests that the interpreted LLD closely corresponds to a residual melt trend left after fractional crystallization (FC) and formation of the cumulate anorthositic rocks and minor apatite–oxide–gabbronorite in shallow magma chambers. Consequent equilibrium crystallization (EC) of separate monzodioritic residual magma batches can produce the observed mineral assemblages and the low Mg numbers measured from olivine (Fo25–45) and pyroxenes (En48–63, Mg#cpx 60–69). The monzodioritic rocks and apatite–oxide–gabbronorites show similar petrological and geochemical characteristics to corresponding rock types in other AMCG suites, and the model described in this study could be applicable to them as well. Peer reviewed